2003
DOI: 10.3354/meps250125
|View full text |Cite
|
Sign up to set email alerts
|

Variability of phytoplankton and mesozooplankton biomass in the subtropical and tropical Atlantic Ocean

Abstract: Data from over 40 yr of expeditions to the Atlantic Ocean are summarised in the form of macroscale contour maps between 40°N and 40°S. The chl a concentrations from the surface and mesozooplankton in the upper layer (0 to 100 m) were analysed from 3992 casts and 1124 hauls respectively. General agreement between chlorophyll concentrations and mesozooplankton biomass distributions was noted on an ocean basin scale. There were non-linear relationships between mean chlorophyll concentration within the 0 to 10 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
6
15
0
1
Order By: Relevance
“…The vertical distribution and photic layer-integrated values of chl a concentration in our study agreed closely with the results reported by for the NASE province, based on an analysis of 18 stations visited in spring and autumn. Similarly, our measurements of mesozooplankton biomass generally fell within the seasonal trend that Finenko et al (2003), using an extensive data set collected over a 40 yr period, reported for the tropical North Atlantic Ocean (Fig. 4).…”
Section: Seasonal Variability and Data Representativenesssupporting
confidence: 86%
“…The vertical distribution and photic layer-integrated values of chl a concentration in our study agreed closely with the results reported by for the NASE province, based on an analysis of 18 stations visited in spring and autumn. Similarly, our measurements of mesozooplankton biomass generally fell within the seasonal trend that Finenko et al (2003), using an extensive data set collected over a 40 yr period, reported for the tropical North Atlantic Ocean (Fig. 4).…”
Section: Seasonal Variability and Data Representativenesssupporting
confidence: 86%
“…Our DW values recalculated for the 0-100 m layer and expressed in g m )2 (0.94-3.38 g m )2 ) are higher than those obtained in the equatorial Atlantic during summer by Le , but differences can be explained by the temporal hydrological variability previously observed in the Atlantic upwelling (Voituriez et al, 1982), tropical regions (Vinogradov, 1997) and areas of enhanced water dynamics activity (Piontkovski & Williams, 1995). Mean DW found during P3 in the upper 200 m, lowest at 4°N and highest at 0°(5.4 mg m )3 and 20.1 mg m )3 , respectively), were within the range of biomass estimated in the subtropical and tropical Atlantic (Finenko et al, 2003) and in the Northern Equatorial Current off West Africa by : 4 to >20 mg m )3 with a maximum of 52.6 near the equator. Compared to studies carried out in the Pacific during and out of instability wave periods Le Borgne et al, 2003), our mean DW values at 2°N during the wave (476 mg C m )2 ) are within the mean biomass range measured by Roman et al (1995) in the Pacific during a tropical instability wave: 492 mg C m )2 with a peak around 800 mg C m )2 .…”
Section: Hydrobiological Characteristicssupporting
confidence: 54%
“…In coastal areas, taxonomic composition of zooplankton is strongly related to the different hydrological seasons (Binet, 1977(Binet, , 1978. In oceanic areas, most data on zooplankton size-structure and relationships within the pelagic community were collected from Russian expeditions in tropical and subtropical zones (Finenko et al, 2003;Piontkovski et al, 2003a). Studies on links between hydrological structures and fisheries are few and only concern specific zones such as the thermo-haline front off Cape Lopez (Dufour & Stretta, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…PIONTKOVSKY et al (2003) analyzed samples from expeditions conducted between 1963 and 1999 and confirmed the patterns of zooplankton biomass on a macroscale in the anticyclonic gyre of the South Atlantic with the majority of the data between 10 °S and 10 °N. FINENKO et al (2003) also analyzed 30 years of data from expeditions in the region and found seasonal variations in the biomass patterns of the tropical and subtropical Atlantic, although limited data were found on the central gyre of the South Atlantic.…”
Section: Introductionmentioning
confidence: 95%